Exploration of Recitation Program for Improving Student's Physics Concept: Study Literature - Shodiqin, Muhammad Ibnu; Pyng, How Shwu (Sekolah Pascasarjana Universitas Negeri Malang (UM), 2025)
The main goal of learning physics is to help students master concepts. Students must possess a strong mastery of concepts, particularly fundamental ones in physics, to effectively solve problems. However, many students struggle with understanding physics concepts. A recitation program can enhance students' mastery of physics concepts. Using the recitation program increases students' concept mastery. This article examines how the program was developed. This research employs a literature review method. Vosviewer processed the data collected from Google Scholar, Scopus, Microsoft Academies, and Harzing's Publish or Perish. The results of the article synthesis show that the recitation program can improve students' mastery of physics concepts, and various kinds of recitation programs have been developed using Wondershare Quiz Creator, Microsoft PowerPoint, and the web. Based on the results of the article synthesis, it can be concluded that the recitation program can improve students' mastery of concepts, and the recitation program that has been developed is getting better and more modern.DOI: 10.17977/jps.v13i12025p032